Tracking Ocean Currents and Surface Temperature in Segara Anakan Lagoon using Drifting Buoy - Isnaini Prihatiningsih; Rizqi Rizaldi Hidayat; Iqbal Ali Husni; Agung Tri Nugroho; Mukti Trenggono; Jatnika Jatnika; Syarief Hidayat (Universitas Diponegoro, 2026)
Ocean currents and sea surface temperature (SST) were recognized as key oceanographic parameters that played a crucial role in understanding coastal and marine physical processes. Despite their importance, real-time monitoring of these variables in narrow and dynamic waterways remained limited. This study designed, developed, and evaluated a low-cost drifting buoy system for the real-time measurement of ocean currents and SST. The buoy integrated temperature sensors and a Global Positioning System (GPS) module, with LoRa technology enabling reliable long-range data transmission. GPS validation revealed a positional error of only 1–2 meters, even in challenging environments with dense urban or vegetative obstructions. Temperature sensor calibration against a standard thermometer yielded an R² value of 0.9989, indicating an exceptionally strong correlation. Field measurements in Segara Anakan Lagoon recorded SST values that fluctuated between 28.5°C and 29.37°C, reflecting typical tropical coastal conditions. Current speeds ranged from 0.052 to 0.78 m/s, with a distinct tidal influence: flows moved landward into the estuary during high tide and seaward during low tide. The results confirmed that the buoy was an effective, accurate, and practical tool for nearshore oceanographic monitoring, particularly in remote or data-scarce regions.